Study Influence of Silver Nanoparticles on Growth Rate of Plant Pathogens: Rhizoctonia Solani, Alternaria Alternata, Fusarium Solani, Fusarium Oxysporum, Aspergillus terreus, Aspergillus Parasiticus, and Bio Agent Trichoderma Harzianum (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study was carried out in (Al-qasim green University / College of Agriculture)on poisons media by Silver Nano particular of levels (0, 10, 15, 20, 25, 30) µl/ml to mea- sured First (FGR), second (SGR) and third growth rate (TGR) of seven fungi Rhizoctonia solani, Alternaria alternata, Fusarium solani, Fusarium oxysporum, Aspergillus Terreus, Aspergillus parasiticus, and Bio agent Trichoderma harzianum which isolated from agri- cultural field of pepper plant, the result showed a significant effect of Ag Nps at 30, 25, 20, 15, 10 µl /ml to inhibition growth rate of all fungi FGR (4.190, 4.904, 5.476, 6.333, 7.190) mm/day, respectively on SGR (9.571, 12.240, 12.810, 14.857, 18.095) mm/day respectively, TGR (12.430, 13.810, 14.100 16.048, 18.095) mm/day respectively com- pared to 0.0 µl /ml .  The results also revealed that T.harzianum was faster growth rate  at FGR, SGR and TGR it was (10.388, 34.722 and 32.333) mm/day, respectively flowed by R.solani, which were (13.055, 30.222 and 29.833) mm/day respectively compared to A.alternata, F.solani, F.oxysporum, A.terreus, A.parasiticus.